Air flow and product arrangement in food freezing environment: a review - Kumar, Sanoj; Kumar, Ashok; Kumar , Satish (Journal of Postharvest Technology, 2018)
In food industries, the production capacity is strongly influenced by the rate of heat transfer in processes such as cooling, freezing, baking, drying, toasting, thawing or chilling. A higher rate of heat transfer can increase the production rate and may improve the quality of processed foods. In freezing processes, a faster freezing rate ensures the safety of the product against microbial growth and contamination. The convective heat flow is enhanced as the fluid motion increases. Air blast cooling processes are majorly ruled by the convective heat transfer, which relates the amount of transferred energy from the product surface to the cooling air. Wide variations in convective heat transfer coefficients may occur in different positions. This work reviews the effect of air flow and product arrangement on food freezing process because of their effect on the convective heat transfer coefficient.